The role of neuroinflammation in the transition of acute to chronic pain and the opioid-induced hyperalgesia and tolerance - Echeverria-Villalobos, Marco; Tortorici, Victor; Brito, Beatriz E.; Ryskamp, David; Uribe, Alberto; Weaver, Tristan (Frontiers in Pharmacology, 2023)
Current evidence suggests that activation of glial and immune cells leads to increased production of proinflammatory mediators, creating a neuroinflammatory state. Neuroinflammation has been proven to be a fundamental mechanism in the genesis of acute pain and its transition to neuropathic and chronic pain. A noxious event that stimulates peripheral afferent nerve fibers may also activate pronociceptive receptors situated at the dorsal root ganglion and dorsal horn of the spinal cord, as well as peripheral glial cells, setting off the so-called peripheral sensitization and spreading neuroinflammation to the brain. Once activated, microglia produce cytokines, chemokines, and neuropeptides that can increase the sensitivity and firing properties of second-order neurons, upregulating the signaling of nociceptive information to the cerebral cortex. This process, known as central sensitization, is crucial for chronification of acute pain.Immune-neuronal interactions are also implicated in the lesser-known complex regulatory relationship between pain and opioids. Current evidence suggests that activated immune and glial cells can alter neuronal function, induce, and maintain pathological pain, and disrupt the analgesic effects of opioid drugs by contributing to the development of tolerance and dependence, even causing paradoxical hyperalgesia. Such alterations may occur when the neuronal environment is impacted by trauma, inflammation, and immune-derived molecules, or when opioids induce proinflammatory glial activation. Hence, understanding these intricate interactions may help in managing pain signaling and opioid efficacy beyond the classical pharmacological approach.